Effect of nitrogen and phosphorus rates on growth, yield and oil content of lemongrass (Cymbopogon flexuosus L.) - E. Elkashif, Mohamed; A. M. Osman, Amani (Gezira Journal of Agricultural Science; Vol 10 No 2 (2012), 2023)
Lemongrass ( Cymbopogon flexuosus L.) is one of the most important medicinal plants because it produces an essential oil which has a high economical value. It is a tropical grass which can be successfully produced in Sudan at the commercial level.  This study was carried out to investigate the effect of N and P fertilizers on vegetative growth, herbage yield and oil content of lemongrass ( Cymbopogon flexuosus L.). The experiment was conducted at the Experimental Farm of the Faculty of Agricultural Sciences, University of Gezira, Wad Medani, Sudan. Treatments consisted of three levels of N (0, 43 and 86 kg N ha -1 ) and two levels of P (0 and 41 kg P 2 O 5 ha -1 ). The treatments were arranged in a randomized block design with four replicates. Application of N and P had significant effects on vegetative growth, herbage yield and oil content in both cuts. The best results were obtained by the application of 86 kg N ha -1 in combination with 41 kg P 2 O 5 ha -1 in both cuts, and the control treatment resulted in the lowest values. Lemongrass oil content was higher in the first cut as compared to the second cut.